Políticas de estabilización y los costos de dolarizar - Schumitt-Grone , Stephanie (2020)
His paper compares the welfare costs of business eycles in a dollarized economy to those arising ín economics with different monctary arrangements, The alternative monetary policy regimes studied belong to threc broad families: devaluation rate rules, inflation targeting, and money growth rate rales. he analysis is conducted within an optimizing model ol a small open economy with stiexy prices. The model is calibrated to the Mexican economy and is driven by three external shocks: terms of trade. world interest rate, and import-price inflation, We show cconometrically that these shocks explain at a minimum 45 percent of the observed forecasting error vartance of Mexican output and the Mexican real exchange rate at £- to L6-quarter horizons. Uhe madel fis the data relatively well to the sense that it can account for the volatility and comovements of key macroeconomic indicators such as output, consumption. inflation, and the real exchange rate. The welfare comparisons suggest that dollarization is the least successful of the monetary policy rules considered: agents are willing to give up between 0.1